Rancang Bangun Sistem Informasi Manajemen Surat Tugas Berbasis Web Menggunakan Waterfall Model - Agus Cahyo Nugroho (Jurnal Informatika: Jurnal Pengembangan IT, 2019)
Letter of Assignment is something that can’t be separated in the management of University. A lecturer works on a specific task based on the assignment letter he receives from either the Department Leader or the University Leader. In the Department this matter is handled by the Department Administrator who handles the operations of the Department daily. If this is still handled manually, of course it will bother the Department Administrator. Especially when Department Administrator workload is high causing human error to occur. Web-based Letter of Assignment Information System is the solution to this problem. This system is developed to facilitate the operation of the Department. Besides documents that are already in digital form make it easy in terms of storage and distribution. So that both the Department Administrator and the Lecturer can access the assignment letter from wherever he is as long as there is still an internet connection. This system was developed using the Waterfall Model method which is one of the classic and most popular methods in software development. Research conducted based on qulitative analysis of primary and secondary data sources with methods of collecting data through observation, interviews and documentation. The implementation of this system is succeeded to facilitate operations in the Department so that the Department Administrator can work more effectively and efficiently.